The territory w and related titles during the middle kingdom and second intermediate period - Russo, Barbara, 1975- (GHP Egyptology ;, 2010)
"This monograph is an in-depth study on the administrative title 'district overseer' (imy-r w) and the term 'district' or 'rural district' (w) in the Egyptian Middle Kingdom (about 2050 to 1650 BC). The sources demonstrate that the territory 'w' was created for some particular administrative needs at the end of the First Intermediate Period. From the historical point of view the management of the 'w' fits the organisation of the society created in this period. The title is still attested in the later Middle Kingdom but lost it importance. The book contains detailed discussions on the title holders and the attestations of 'w'." -- Publisher's website, viewed Dec. 21, 2010.